Successful Treatment of Aortic Coarctation in an Extremely Low Birth Weight Infant with Balloon Angioplasty - Arici, Galip; Kaya, Özkan; Kavgacı, Akif; Akduman, Hasan; Örün, Utku Arman (Zeitschrift für Geburtshilfe und Neonatologie, 2024)
In our case report, we present a case of successful antegrade balloon angioplasty performed via the femoral vein on a 980-gram neonate with severe coarctation of the aorta. Upon reviewing the literature, we found no cases of balloon angioplasty for coarctation performed via the femoral vein in infants with a lower birth weight than in our case. Our aim is to underline that each patient may require individual evaluation and management options.
Keywords: aortic coarctation; balloon angioplasty; extremely low birth weight infant